‘Do as I Say not as I Do’: EUtopia, the Ceecs and the Credibility of the EU Human Rights Regime - Ingi Iusmen (Romanian Journal of European Affairs)
This article examines EU’s involvement in human rights from the perspective of a promoter of human rights norms. It is argued that a human rights EUtopia has emerged, i.e. there is a gap between the real and normative EU -when it comes to human rights – which affects the credibility of the EU’s human rights regime. The EU lacks a solid legal entrenchment of human rights and there are different degrees of human rights protection in the Member States which amount to different hierarchical concepts of human rights. There are legal shortcomings regarding EU’s human rights promotion to third countries, while the Copenhagen human rights conditionality attached to EU accession was vaguely stated and was not underpinned by EU internal human rights templates. Furthermore, the screening process of the candidates- by the use of double standards – entailed EU’s involvement in matters falling outside its own internal remits. Hence the credibility of the EU human rights regime is jeopardised by its attempt to export human rights externally– hence the normative and utopian claims – without having a real, substantial legal entrenchment of human rights internally.